Left ventricular assist device-related infections and the risk of cerebrovascular accidents: a EUROMACS study. (23rd August 2022) - Zijderhand, Casper F; Antonides, Christiaan F J; Veen, Kevin M; Verkaik, Nelianne J; Schoenrath, Felix; Gummert, Jan; Nemec, Petr; Merkely, Béla; Musumeci, Francesco; Meyns, Bart; de By, Theo M M H; Bogers, Ad J J C; et al.
Abstract: OBJECTIVES: In patients supported by a durable left ventricular assist device (LVAD), infections are a frequently reported adverse event with increased morbidity and mortality. The purpose of this study was to investigate the possible association between infections and thromboembolic events, most notable cerebrovascular accidents (CVAs), in LVAD patients. METHODS: An analysis of the multicentre European Registry for Patients Assisted with Mechanical Circulatory Support was performed. Infections were categorized as VAD-specific infections, VAD-related infections and non-VAD-related infections. An extended Kaplan–Meier analysis for the risk of CVA with infection as a time-dependent covariate and a multivariable Cox proportional hazard model were performed. RESULTS: For this analysis, 3282 patients with an LVAD were included with the majority of patients being male (83.1%). During follow-up, 1262 patients suffered from infection, and 457 patients had a CVA. Cox regression analysis with first infection as time-dependent covariate revealed a hazard ratio (HR) for CVA of 1.90 [95% confidence interval (CI): 1.55–2.33; P  <   0.001]. Multivariable analysis confirmed the association for infection and CVAs with an HR of 1.99 (95% CI: 1.62–2.45; P  <   0.001). With infections subcategorized, VAD-specific HR was 1.56 (95% CI: 1.18–2.08; P 0.002) and VAD-related infections [HR: 1.99 (95% CI: 1.41–2.82; P  <   0.001)] remained associated with CVAs, while non-VAD-related infections ( P = 0.102) were not. CONCLUSIONS: Infection during LVAD support is associated with an increased risk of developing an ischaemic or haemorrhagic CVA, particularly in the setting of VAD-related or VAD-specific infections. This suggests the need of a stringent anticoagulation management and adequate antibiotic treatment during an infection in LVAD-supported patients. Abstract : Continuous-flow left ventricular assist devices (LVADs) have become an important modality, especially in the high income countries, in the treatment of end-stage heart failure (HF) as a bridge to transplantation, a bridge to candidacy or destination therapy.